Beyond the Page: A Process Review of Using Ethnodrama to Disseminate Research Findings. Issue 6 (3rd June 2017) - Taylor, Jamilah; Namey, Emily; Carrington Johnson, Annette; Guest, Greg
Abstract : Public health researchers are charged with communicating study findings to appropriate audiences. Dissemination activities typically target the academic research community. However, as participatory research grows, researchers are increasingly exploring innovative dissemination techniques to reach broader audiences, particularly research participants and their communities. One technique is ethnodrama/ethnotheatre, a written or live performance based on study findings. Though used effectively in social change programs, dramas are seldom used to distribute research findings exclusively. Therefore, little information is available about planning and implementing an ethnodrama for this purpose. We present a case study describing the process of planning and implementing an ethnodrama in the context of the Durham Focus Group Study, which explored men's health-seeking behaviors and experiences with health and healthcare services in Durham, North Carolina. Here, we highlight lessons learned throughout the production of the ethnodrama, and how we addressed challenges associated with transforming research data into educational entertainment. Additionally, we provide discussion of audience feedback, which indicated that our ethnodrama evoked an urgency to change health behaviors among lay persons (67%) and delivery of health services among those identifying as providers (84%), pointing to the success of the performance in both entertaining and educating the audience.